2019
DOI: 10.1002/med.21561
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase‐B inhibitors as potential neurotherapeutic agents: An overview and update

Abstract: Monoamine oxidase (MAO) inhibitors have made significant contributions and remain an indispensable approach of molecular and mechanistic diversity for the discovery of antineurodegenerative drugs. However, their usage has been hampered by nonselective and/or irreversible action which resulted in drawbacks like liver toxicity, cheese effect, and so forth. Hence, the search for selective MAO inhibitors (MAOIs) has become a substantial focus in current drug discovery. This review summarizes our current understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 269 publications
(704 reference statements)
0
50
0
Order By: Relevance
“…[ 4 ] Furthermore, considerations of the importance of monoaminergic signalling in the biogenic amine deficiencies indicate that MAOs could be involved in the regulation of mood and cognitive function. [ 5 ] Based on knowledge of the homology and catalytic mechanisms of MAO‐A and B, several research groups have focused on the design and development of selective MAO inhibitors, and available evidence indicates MAO‐A and MAO‐B are important drug targets for the treatment of neuropsychiatric and neurodegenerative disorders like anxiety, depression, Alzheimer's disease (AD) and Parkinson's disease (PD). [ 6 ] Oxidative deamination by MAO‐B usually generates ammonia, hydrogen peroxide and various aldehydes as by‐products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] Furthermore, considerations of the importance of monoaminergic signalling in the biogenic amine deficiencies indicate that MAOs could be involved in the regulation of mood and cognitive function. [ 5 ] Based on knowledge of the homology and catalytic mechanisms of MAO‐A and B, several research groups have focused on the design and development of selective MAO inhibitors, and available evidence indicates MAO‐A and MAO‐B are important drug targets for the treatment of neuropsychiatric and neurodegenerative disorders like anxiety, depression, Alzheimer's disease (AD) and Parkinson's disease (PD). [ 6 ] Oxidative deamination by MAO‐B usually generates ammonia, hydrogen peroxide and various aldehydes as by‐products.…”
Section: Introductionmentioning
confidence: 99%
“…The HBA or HBD groups may be present in the linker, which can connect with hydrophobic nucleus or hydrophobic zone of the inhibitors. [ 5,37 ] We considered that the presence of the two hydrophobic pharmacophoric features linked with an amide‐connected olefinic spacer in enamides would result in recognition by the inhibitor binding cavity of MAO‐B. Recently, some amides have been reported to exhibit potent selective MAO‐B inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The molecules with reversible selective inhibition of MAO-A or MAO-B have therapeutic potential for the treatment of neurological and psychiatric disorders, especially caused due to depletion of neurotransmitter biogenic amines [9,29,30]. Previous studies from our lab have reported selective inhibition of human MAO-B with flavonoid natural products [18][19][20].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, there is still a pressing medical need for the development of reversible selective MAO-B inhibitors with effectiveness and safety for long-term use to treat PD [ 112 ]. Selegiline and rasagiline are irreversible MAO-B inhibitors with undesirable adverse effects, including hallucination and headache, the production of neurotoxic or ineffective metabolites, and gradual short-lived action after long-term use.…”
Section: Recent Advances In the Preclinical Study Of Dopaminergic Drumentioning
confidence: 99%